2013
DOI: 10.1158/1078-0432.ccr-12-2459
|View full text |Cite
|
Sign up to set email alerts
|

Topotecan and Doxorubicin Combination to Treat Recurrent Ovarian Cancer: The Influence of Drug Exposure Time and Delivery Systems to Achieve Optimum Therapeutic Activity

Abstract: Purpose: To provide proof-of-concept data to support use of Doxil-liposomal topotecan (Topophore C) combinations to treat ovarian cancer.Experimental Design: ES-2, OVCAR-3, and SKOV-3 ovarian cancer cell lines were treated with doxorubicin-topotecan combinations by exposing the cells to drugs from 1 to 72 hours. Pharmacokinetic analysis was conducted following administration of liposomal formulations of these drugs alone and in combination. Efficacy assessments were completed in ES-2 and SKOV-3 ovarian cancer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…The result revealed that RASSF1A is absent in SKOV-3 and OVCAR-3 cells, while it is present in the HO8910 and HO8910PM cells. Our findings are consistent with those of a previous study showing that SKOV-3 and OVCAR-3 cells represent an ovarian cancer, referred to as serous adenocarcinoma (28). We subsequently transfected SKOV-3 cells with an adenovirus with or without RASSF1A and the expression of RASSF1A in the differently treated SKOV-3 cells was analyzed.…”
Section: Discussionsupporting
confidence: 91%
“…The result revealed that RASSF1A is absent in SKOV-3 and OVCAR-3 cells, while it is present in the HO8910 and HO8910PM cells. Our findings are consistent with those of a previous study showing that SKOV-3 and OVCAR-3 cells represent an ovarian cancer, referred to as serous adenocarcinoma (28). We subsequently transfected SKOV-3 cells with an adenovirus with or without RASSF1A and the expression of RASSF1A in the differently treated SKOV-3 cells was analyzed.…”
Section: Discussionsupporting
confidence: 91%
“… Li & Howell (2010) and Patankar et al (2013) used different doses of chemotherapeutics in the treatment group and control group. Therefore, it was tested whether these studies were responsible for the positive overall outcome.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Drug Combination Database (DCDB) [ 4 ], there have been 330 FDA-approved and 1033 investigational drug combinations until the second version. With more and more researches on this new form of therapy, drug combinations have been proven a promising way to combat complex diseases [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%